Association between multimorbidity and having less than 20 natural teeth among Chinese older adults: a cross-sectional study - Yi Wu; Hui Liu; Yue Qin; HaoRan Chen; Junling Ma; Mei Yin; Lei Shi; Yang Fu (Scientific Reports)
Abstract Understanding the impact of multimorbidity on having less than 20 natural teeth is crucial for safeguarding the oral health of older adults with multimorbidity. This study aimed to analyze the association between multimorbidity and having less than 20 natural teeth in older Chinese adults. The data for this analysis were obtained from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), which covers 23 provinces, municipalities, and autonomous regions throughout China. The survey includes information on dental health (such as dentition status), a variety of chronic conditions, and other sociological characteristics of older adults in China. Having less than 20 natural teeth was used as the dependent variable, with multimorbidity as the independent variable. A multivariable logistic regression model was applied to estimate the association between multimorbidity and having less than 20 natural teeth. A total of 3,640 older adults were included in the study, of whom 58.27% (2121) were identified as having less than 20 natural teeth. The results indicated that factors such as age, education level, exercise, ability to perform daily activities, frequency of brushing teeth, and BMI are associated with having less than 20 natural teeth. Additionally, compared with those without chronic disease, the odds ratio (OR) of having less than 20 natural teeth was 1.32 (95% CI: 1.10, 1.57) for older adults with only one chronic disease, and the OR for those with two or more chronic diseases was 1.418 (95% CI: 1.06, 1.89). This study highlights the importance of monitoring the oral health of older adults with multimorbidity and identifies an association between multimorbidity and having less than 20 natural teeth. Oral health care institutions should implement measures to support the development of more comprehensive public health policies.